SISTEM INFORMASI PENJUALAN BERBASIS WEB DENGAN METODE ADDIE PADA KEDAI KOPI KARAWANG - Eko Martantoh; Maulana Aripudin (Journal of Innovation And Future Technology (IFTECH), 2023)
Buying and selling is an activity which requires the accuracy of calculating the profit earned and also being able to avoid losses. This is often constrained by inaccurate calculation tools that lead to unclear profit acquisition. Collection organizations can provide easy sales calculations available for example in the form of a system. This research develops a web-based sales information system to carry out sales calculations as well as digitize cashier calculations. This web-based sales information system was developed using the CodeIgniter framework. This research is a type of research and development (Research and Development) with the ADDIE method which consists of the stages of analysis (Analysis), design (Design), development (Development), at the stage of implementation (Implementation), evaluation (Evaluation) has not been carried out. The data collection method uses a questionnaire. The results of testing the 5 aspects in it, such as content aspects, design aspects, usability aspects, portability aspects and maintainability aspects based on the Addie method obtained satisfactory results. Based on the analysis of test results by respondents, this sales information system is in accordance with the Addie method that is currently being implemented. Suggestions for further research can carry out the implementation and evaluation stages, and add system facilities to make it more complete.